National Security Intelligence and Ethics - Miller, Seumas; Regan, Mitt; Walsh, Patrick F. (Studies in Intelligence, 2022)
This volume examines the ethical issues that arise as a result of national security intelligence collection and analysis. Powerful new technologies enable the collection, communication, and analysis of national security data on an unprecedented scale. Data collection now plays a central role in intelligence practice, yet this development raises a host of ethical and national security problems, such as: privacy; autonomy; threats to national security and democracy by foreign states; and accountability for liberal democracies. This volume provides a comprehensive set of in-depth ethical analyses of these problems by combining contributions from both ethics scholars and intelligence practitioners. It provides the reader with a practical understanding of relevant operations, the issues that they raise, and analysis of how responses to these issues can be informed by a commitment to liberal democratic values. This combination of perspectives is crucial in providing an informed appreciation of ethical challenges that is also grounded in the realities of the practice of intelligence. This book will be of great interest to all students of intelligence studies, ethics, security studies, foreign policy, and International Relations.